Deposition of impurity metals during campaigns with the JET ITER-like Wall. (May 2019) - Widdowson, A.; Coad, J.P.; Alves, E.; Baron-Wiechec, A.; Catarino, N.; Corregidor, V.; Heinola, K.; Krat, S.; Makepeace, C.; Matthews, G.F.; Mayer, M.; Mizohata, K.; et al.
Abstract: Post mortem analysis shows that mid and high atomic number metallic impurities are present in deposits on JET plasma facing components with the highest amount of Ni and W, and therefore the largest sink, being found at the top of the inner divertor. Sources are defined as "continuous" or "specific", in that "continuous" sources arise from ongoing erosion from plasma facing surfaces and "specific" are linked with specific events which decrease over time until they no longer act as a source. This contribution evaluates the sinks and estimates sources, and the balance gives an indication of the dominating processes. Charge exchange neutral erosion is found to be the main source of nickel, whereas erosion of divertor plasma facing components is the main source of tungsten. Specific sources are shown to have little influence over the global mid- and high-Z impurity concentrations in deposits.